2011
DOI: 10.1021/jp2074489
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Conformational Changes in a G-Quadruplex of Thrombin-Binding Aptamer Induced by Pb2+

Abstract: It has been shown that guanine-rich DNA can fold into a G-quadruplex with certain metal cations. The spectral characteristics, thermostability, and kinetics for the formation of a Pb(2+)-driven G-quadruplex of thrombin-binding aptamer (TBA) were measured in the current work using a combination of ultraviolet (UV) and circular dichroism (CD) spectroscopy along with stopped-flow technique. CD spectra demonstrated that TBA could fold into a unique G-quadruplex with a strong positive peak at 312 nm. Analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 49 publications
5
46
0
Order By: Relevance
“…In short, the initially added Na + ions have a synergetic effect with Pb 2+ ions on the structural transition of the PS2.M chain, whereas the K + ions have a competitive effect on this transition. This result is quite consistent with those of the previous studies (45).
Figure 7.Proposed mechanism of the structural transition in a G-quadruplex of PS2.M induced by Pb 2+ ions.
…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In short, the initially added Na + ions have a synergetic effect with Pb 2+ ions on the structural transition of the PS2.M chain, whereas the K + ions have a competitive effect on this transition. This result is quite consistent with those of the previous studies (45).
Figure 7.Proposed mechanism of the structural transition in a G-quadruplex of PS2.M induced by Pb 2+ ions.
…”
Section: Resultssupporting
confidence: 94%
“…These relaxation times are much shorter than those of the G-quadruplexes induced by monovalent cations (34,44), which may be partly due to the higher charge of the Pb 2+ ions. As expected, the folding rates are independent of the concentration of Pb(NO 3 ) 2 , suggesting rate-saturation kinetics, which is in accordance with the high stability of the Pb 2+ -induced G-quadruplex (45). Recently, a simulation study (46) on the binding of cations to G-rich DNA showed that it is a complex multiple pathway process, which is strongly affected by the type of the cations.…”
Section: Resultssupporting
confidence: 84%
“…In contrast, the biologically relevant divalent cations Mg 2+ and Ca 2+ had no effect on RNA G4 stability. However, the data also may suggest that other divalent cations, such as harmful heavy metals (Pb 2+ , Cd 2+ or Hg 2+ ), may bind and disturb G4 structures contributing to their toxicity; such binding is reported for guanine-rich oligos 30; 31 .…”
Section: Similarities and Differences Between Rna And Dna G-quadruplexesmentioning
confidence: 95%
“…Micromolar concentrations of Pb 2+ induce the formation of DNA G-quadruplexes even in the absence of K + or Na + , the two most common cations associated with G-quadruplexes. Pb 2+ -stabilized G-quadruplexes adopt a more compact structure than those stabilized by monovalent cations due to the smaller size and high charge density of Pb 2+ 6a,10,11,12a,b . We wondered whether these observations extend to the RNA G-quadruplex in Spinach.…”
mentioning
confidence: 99%